Atlastin-mediated membrane tethering is critical for cargo mobility and exit from the endoplasmic reticulum - Niu, Liling (Proc Natl Acad Sci U S A, 2019)
Endoplasmic reticulum (ER) membrane junctions are formed by the dynamin-like GTPase atlastin (ATL). Deletion of ATL results in long unbranched ER tubules in cells, and mutation of human ATL1 is linked to hereditary spastic paraplegia. Here, we demonstrate that COPII formation is drastically decreased in the periphery of ATL-deleted cells. ER export of cargo proteins becomes defective; ER exit site initiation is not affected, but many of the sites fail to recruit COPII subunits. The efficiency of cargo packaging into COPII vesicles is significantly reduced in cells lacking ATLs, or when the ER is transiently fragmented. Cargo is less mobile in the ER in the absence of ATL, but the cargo mobility and COPII formation can be restored by ATL R77A, which is capable of tethering, but not fusing, ER tubules. These findings suggest that the generation of ER junctions by ATL plays a critical role in maintaining the necessary mobility of ER contents to allow efficient packaging of cargo proteins into COPII vesicles.